2006
DOI: 10.1177/0361198106196900111
|View full text |Cite
|
Sign up to set email alerts
|

Road Safety Audits

Abstract: Road safety audits (RSAs) are emerging as an effective tool for proactively improving the safety performance of a road project while it is still in the design or planning stage or for identifying and mitigating safety concerns in existing transportation infrastructure. The authors are nearing the end of a yearlong series of nine pilot RSAs conducted across the United States, sponsored by FHWA's Office of Safety Design and conducted for a variety of agencies at the local (county, city, and tribal) and state lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the United States, the state government establishes road-safety policies, is responsible for safety management such as regulations, and implements post-improvement measures in a continuous manner [9][10][11]. In recent years, there have been many cases of utilizing road traffic-safety-management systems as suggested in ISO 39001 [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the state government establishes road-safety policies, is responsible for safety management such as regulations, and implements post-improvement measures in a continuous manner [9][10][11]. In recent years, there have been many cases of utilizing road traffic-safety-management systems as suggested in ISO 39001 [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The most important part, however, is to share the observations and findings of RSA with the transportation sector. In a study, Gibbs et al ( 21 ) suggested that publishing RSA case studies can provide local and state agencies with examples and offer further guidance which can assist them in implementing RSAs and proposing countermeasures at their jurisdictions facing similar safety issues.…”
mentioning
confidence: 99%